The impact of platformization in brazilian alternative media seenthrough user-generated content - Silveira, Stefanie Carlan da (2024)
This study addresses the platform’s impact on the production and dissemination of User Generated Content (UGC) in Brazilian alternative media and its influence on the ability to reach audiences in this country. It seeks to understand the growing presence of UGC on social media platforms that reflects expanded opportunities for online participation, attracting historically marginalised groups and allowing alternative media to mobilise individuals and share their productions. The observation of multiple cases and content analysis are used, focusing on the publications of UGC videos on the Instagram accounts of two Brazilian alternative media, Jornalistas Livres and Mídia NINJA. The study was conducted in October 2022, before the Brazilian presidential election. The results revealed a significant dependence on alternative media in the UGC, representing around 40 % of the publications analysed. The intersection between platforms and alternative media presents challenges and opportunities; while it expands visibility and range, it can also restrict autonomy. Ultimately, this study highlights how alternative journalism outlets react to the challenges and opportunities associated with these digital infrastructures.